So Far But Still So Near: The Case of the Ebola Scare on Informal Trade in Zimbabwe - Tarisayi, Kudzayi Savious (International Journal For Research In Health Sciences And Nursing, 2015)
This paper seeks to explore the impact of the Ebola scare on informal clothing traders in Zimbabwe despite the distance from West Africa. When there was the outbreak of Ebola in West Africa in February 2014, concerns were raised on various platforms on informal trade in Africa in general and the influx of second-hand clothing into Zimbabwe in particular. Government announcements in Zimbabwe fuelled speculation on social media on the likely threat posed by second-hand clothes in spreading Ebola. It is against this background that this research sought to examine the impact of the Ebola scare on informal traders at Chitima Market in Masvingo. The researcher purposively sampled and interviewed informal traders at Chitima Market. The research revealed that the Ebola scare negatively impacted on the demand and prices of second-hand clothing and therefore income of the informal traders.